2012
DOI: 10.4161/jig.23738
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic endoscope imaging (ScopeGuide) elucidates the mechanism of action of the pain-alleviating impact of water exchange colonoscopy - attenuation of loop formation

Abstract: MEI data objectively demonstrated significantly fewer loops during water exchange colonoscopy, elucidating its mechanism of pain alleviation - attenuation of loop formation. Since MEI feedback enhances cecal intubation by trainees, the role of MEI combined water exchange in speeding up trainee learning curves deserves further evaluations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 22 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…Use of MEI could potentially explain why WE produced a signifi cant reduction of pain during colonoscopy ( 31 ). Indeed, MEI objectively demonstrated signifi cantly fewer loops during WE colonoscopy, explaining pain alleviation by attenuation of loop formation ( 32 ). Th e current data showed that the length of the colonoscope inside the patient when the tip reached the cecum in the WE group was signifi cantly shorter than that in the WI group ( Table 2 ), which was consistent with less looping.…”
Section: Air Insufflation Vs Water Immersion and Exchangesupporting
confidence: 56%
“…Use of MEI could potentially explain why WE produced a signifi cant reduction of pain during colonoscopy ( 31 ). Indeed, MEI objectively demonstrated signifi cantly fewer loops during WE colonoscopy, explaining pain alleviation by attenuation of loop formation ( 32 ). Th e current data showed that the length of the colonoscope inside the patient when the tip reached the cecum in the WE group was signifi cantly shorter than that in the WI group ( Table 2 ), which was consistent with less looping.…”
Section: Air Insufflation Vs Water Immersion and Exchangesupporting
confidence: 56%
“…There was an added benefit of a ''straighter'' scope with less looping to achieve cecum intubation using WE. 37 Less looping and angulations compared with AI could improve scope tip control and enhance detection of flat lesions.…”
Section: Discussionmentioning
confidence: 99%
“…14 Infusion of water straightens the sigmoid and reduces loop formation at the rectosigmoid junction. 15 A longer and more tortuous colon is more difficult to intubate to the cecum. 10 Water exchange avoids lengthening of the colon associated with air insufflation, and the aspiration of residual air pockets during WE further shortens the colon.…”
Section: Q16mentioning
confidence: 99%